Zoneamento de risco à inundação de Dom Pedrito - RS - Pessotto, Wellerson (2020)
The city of Dom Pedrito is placed on the West border of the Rio Grande do Sul state and has a population of 38.898 inhabitants, with 90% living in the urban area. The Dom Pedrito urban perimeter is placed at the right margin of the Santa Maria River and, 25,6% of the city is affected by flood events. This region is occupied by edifications with different purposes, like living, trade, and services, which at each event of flood are harmed. Therefore, this research has the general purpose of mapping the risk zones of floods in the urban area of Dom Pedrito-RS, which may help the government to manage these events and plan the urban area. The methodology procedures to elaborate this research lies on: build a theoric reference, to ground and sustain the held procedures and help to characterize the study field, and also to make a document survey from the Civil Defense about the events of flood in the city in the period from 1942 to 2019. Thus, to elaborate the risk map, it was used the return time (RT) calculus of the events, which adopted the return times (RT) <1 year, 5, 25 and 75 years. To delimitate the flood susceptible perimeter, it was used the 75 years RT, along with the topographic survey realization to create a Land Digital Model (LDM), bringing precision to the results. The social vulnerability was assessed considering the following variables: edification size, number of floors, material, edification conservation state, apertures conservation state, elevated edifications, open sewer, accumulated garbage, and the rural reproduction. For each variable was attributed a grade and weight considering the level of importance, which lead to a social vulnerability map. The construction of the risk zones maps was obtained through space crossing of danger and social vulnerability data, which yielded in four degrees of risk: very high, high, medium and low. The Getúlio Vargas, Santa Maria, and Sagrada Face neighborhoods find themselves in high and very high danger. Based on the risk zone map were proposed some measures to minimize or eradicate the flood threat, as containment dikes, reforestation of the riverside, environmental education, population support measures, together with other complementary actions. All of these measures were divided into three classes, considering the time for its implementation: short, medium and long term.